1996
DOI: 10.1021/jf950761z
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Scale Extraction of Rice Bran Oil with Dense Carbon Dioxide

Abstract: The purpose of this study was to measure the effects of temperature, pressure, and flow rate of dense CO2 on its ability to extract, refine, and fractionate rice bran oil. Column beds (300 g) of rice bran were extracted with dense CO2 at a flow rate of ∼2.5 kg/h, temperatures of 0−60 °C, and pressures of 17−31 MPa over a period of 6 h. The extracted total oil; the free fatty acid, α-tocopherol, sterols (campesterol, stigmasterol, β-sitosterol), and oryzanol components; together with moisture were measured at i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
32
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 21 publications
8
32
1
1
Order By: Relevance
“…This is justified by the increase in solute vapor pressure with the increase in temperature. These results agree with the results of Shen et al (1996) that the apparent solubility of rice bran oil increases with pressure at 40°C and decreases at higher temperatures. He concludes that rice bran oil is more highly soluble at 310 bar and 40°C and that lower solubilitie's of carbon dioxide favor the separation of free fatty acids and triglicerides.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This is justified by the increase in solute vapor pressure with the increase in temperature. These results agree with the results of Shen et al (1996) that the apparent solubility of rice bran oil increases with pressure at 40°C and decreases at higher temperatures. He concludes that rice bran oil is more highly soluble at 310 bar and 40°C and that lower solubilitie's of carbon dioxide favor the separation of free fatty acids and triglicerides.…”
Section: Resultssupporting
confidence: 92%
“…In the second method, selective separation is achieved through gradual depressurization or gradual heating or cooling of the extract, which allows a controlled fractionation of the extract. Shen et al (1996) assessed the effects of temperature, pressures and extraction time of the rice bran oil on the yield and solute components extracted with subcritical and supercritical CO 2 . The results indicate an increase in the solubility of the rice bran oil by increasing the temperature up to 40ºC and then decreasing it.…”
Section: Introductionmentioning
confidence: 99%
“…At 31.4MPa the lipid yield increased with the extracting temperature (p<0.05). Bhupsesh et al (26) reported that the extracting conditions have an effect on the lipid yield in tomato seed oil extraction. The oil yield increases with pressure.…”
Section: Extraction Of Salmon Roe Lipids With Scf-comentioning
confidence: 99%
“…Extraction of tomato seed oil resulted in a change in the fatty acid profile (26), because of the difference in the fatty acid solubility in SC-CO 2 . Soluble components can be extracted first in SC-CO 2 .…”
Section: Effect Of Extracting Temperature Andmentioning
confidence: 99%
“…For extraction of RBO, attempts using supercritical fluid extractions with CO 2 [2,[13][14][15] and methanol/CO 2 [16] were reported by several groups. A maximum RBO yield of 20.5%, which represents over 99% of lipid recovery, was reportedly obtained with a conventional approach using hexane, while the yield with supercritical CO 2 extraction ranged between 19.2 and 20.4% [2,15].…”
Section: Introductionmentioning
confidence: 99%